WATER AND THE VISCOSITY OF DEPOLYMERIZED ALUMINOSILICATE MELTS - Whittington A.; Richet P.; Holtz F. (My University, 2000)
To determine the effect of water on the rheology of depolymerized melts, we have measured the viscosity of two series of hydrated synthetic aluminosilicate melts analogous in bulk polymerization to tephritic and basanitic liquids. The measurements have been made at 1 atm in the range 108.7 to 1013.7 Pa s, for water contents between 0 and 2.5 wt.% H2O. In all cases, water exerts a marked depressing effect on the viscosity but the reduction is much smaller than for the more polymerized compositions studied previously. With the addition of 2 wt.% H2O, for example, extrapolation of the results suggests that the viscosity decreases by ca. 4.5 and 1.5 orders of magnitude at 900 and 1200 K, respectively. An interesting consequence is that the viscosity and glass transition temperatures of the most polymerized melts become lower than those of depolymerized melts at water contents higher than ca. 1 wt.%. By analogy with natural magmatic compositions, hydrous rhyolites may become less viscous than hydrous basalts at high water contents and low temperatures. In nature, the viscosities of polymerized and depolymerized magmatic liquids should be similar because basalts are emplaced at higher temperatures but rhyolites typically have higher water contents.